DISCOVER - Sarouphim, Ketty M. (1999)
Based on the general framework of Gardner's (1983) theory of multiple intelligence and Maker's (1996) definition of giftedness, the DISCOVER process is a performance-based assessment designed to identify gifted students from culturally diverse groups. The process consists of five activities through which linguistic, logical-mathematical, and spatial intelligences are appraised. In this review, I describe the assessment and review preliminary studies on its reliability and validity. The DISCOVER assessment seems to be a promising alternative technique through which the problem of underrepresentation of gifted minorities in programs for the gifted might be reduced. However, educators using the DISCOVER assessment for identification purposes must make sure that a good match exists between the assessment and the type of gifted program in which students will be placed.